It's getting better all the time. Issue 2 (1st February 2017) - Butman, Samuel M.
Key Points: The risk of target lesion revascularization increases when extensive numbers or lengths of cobalt chromium everolimus‐eluting stents are deployed. There is no relationship between the risk of stent thrombosis to total stent length. Newer stent materials and designs do result in better long‐term outcomes.